The spatial dimension of cycle logistics - Staricco, Luca; Vitale Brovarone, Elisabetta (TeMA - Journal of Land Use, Mobility and Environment, 2016)
Cycle logistics is emerging as a promising alternative in urban freight transport. Compared to fossil fuelled vans, the use of cycles for delivering goods within urban areas offers advantages in terms of environmental friendliness, economic efficiency, flexibility, and liveability of urban neighbourhood. At the same time, cycle logistics has to face limits in terms of weight and volume of goods that can be delivered, distances that can be covered, and spatial urban structures that can be served. This latter issue has till now received less attention in the scientific literature: it is generally recognized that cycle logistics performs at its best in inner urban areas, but no systematic study has been realized to identify specific spatial requisites for the effectiveness of cycle logistics. This paper provides a brief review of the main issues that emerge from the literature over cycle logistics, and contributes to stimulate the debate over the spatial dimension of cycle logistics: it presents a classification of cycle logistics schemes, on the basis of their integration with other urban logistic facilities and of the spatial structure of delivery operations. A three-level classification is proposed, depending on the type of goods consolidation: only distribution without consolidation, consolidation in a fixed urban consolidation centre, or consolidation in a mobile depot; for each level, operational examples and case studies are provided. This systematizing typology could support both public and private operators in decisions about the organization of cycle logistics facilities, such as the location of urban consolidation centres or the composition of cycle fleets.